Effectiveness of Problem Base Learning (PBL) Assisted by Pocket Book to Reading Literacy Skill of Students - indianasari, Indianasari; Suharini, Erni; Handoyo, Eko (Educational Management, 2019)
This research aimed to analyze the use of Problem Based Learning (PBL) assisted by pocket book to reading literacy skill. This quasi experimental research had quantitative method. The population of this research consisted of IV grade of Karangayu 02 in academic 2018/2019. It consisted of 60 studeents grouped into two classes: IV A and IV B. The sampling technique was nonprobabilty sampling with saturated sampling. The data was obtained from pretest – posttest. The data analysis consisted of normality test, homogeneity test, independent sample t-test, and N – gain test. The findings showed that reading mathematics literacy skill of experimental group classically reached 93.1% with average 84.13. Meanwhile, the control group classically reached 73.3% with average score 76.6. The t-test result showed that Problem Based Learning (PBL) assisted by pocket book was effective to reading literacy skill of primary school students. It could be concluded that Problem Based Learning assisted by pocket book was effective to improve reading literacy skill of students. It is suggested to develop further investigation.